Content validation of scales assessing psychological antecedents of crowds among Hajj pilgrims - Abdul Rahman, Shukran; Mohd Mahudin, Nor Diana; Shuib, Mohd Arif; Ahmad Hatta,, Zulkarnain; Abdul Ghani, Noraida; Sulong, Jasni; Mohd Hashim, Intan Hashimah; Mat Saad, Zarina (2014)
The objective of this paper is to report the process of quantifying the content validity of items in five newly developed scales that measure the psychological antecedents of crowds during Hajj (i.e., Personality, Crowd mood, Expected Crowdedness, Perceived Lawlessness, and Hajj Familiarity). The purpose of content validation is to assess whether the items in the scales represent the construct of specific interest, referred to as the concept of content validity for the scales. The content validation exercise helps test developers to assess the extent to which the scale samples or represents all domains of a given concept. A scale may lack content validity if it only assesses a dimension of the construct and fails to take into account the remaining dimensions as have been defined for the respective construct. This exercise quantifies the degree of experts’ agreement (N=15) as to whether the sample of items developed adequately represent a particular dimension of the construct in question, after which the content validity ratio for each item was calculated. The value of content validity ratio serves as important basis for the acceptance of an item in the scales, as it provides the agreement of subject matter experts about the representativeness of the items, and, in turn, leads to the index for high content validity.